2018
DOI: 10.1002/hyp.11495
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall, run‐off, and sediment transport dynamics in a humid mountain badland area: Long‐term results from a small catchment

Abstract: In this study, we investigated rainfall, run-off, and sediment transport dynamics (414 runoff events and 231 events with sediment information) of a humid mountain badland area -the Araguás catchment (Central Pyrenees, Spain)-from October 2005 to September 2016. Use of this long-term database allows characterization of the hydrological response, which consist of low-magnitude/high-frequency events and high-magnitude/ low-frequency events, and identification of seasonal dynamics and rainfall-run-off thresholds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 56 publications
6
27
0
Order By: Relevance
“…This indicates that other factors besides discharge control the SSCs in the study catchment. Other studies have reported similar results in small catchments [10,13,15,21], which are particularly vulnerable to natural and anthropogenic disturbances, such as changes in vegetative cover, debris flow and changes in SS inputs. Daily mean SSCs varied widely during the monitoring period ( Figure 4) and exhibited much more variability than discharge (coefficient of variation 272% vs. 100%).…”
Section: Dynamics In Suspended Sediment Concentrationssupporting
confidence: 67%
See 4 more Smart Citations
“…This indicates that other factors besides discharge control the SSCs in the study catchment. Other studies have reported similar results in small catchments [10,13,15,21], which are particularly vulnerable to natural and anthropogenic disturbances, such as changes in vegetative cover, debris flow and changes in SS inputs. Daily mean SSCs varied widely during the monitoring period ( Figure 4) and exhibited much more variability than discharge (coefficient of variation 272% vs. 100%).…”
Section: Dynamics In Suspended Sediment Concentrationssupporting
confidence: 67%
“…This indicates that other factors besides discharge control the SSCs in the study catchment. Other studies have reported similar results in small catchments [10,13,15,21], which are particularly vulnerable to natural and anthropogenic disturbances, such as changes in vegetative cover, debris flow and changes in SS inputs. With regard to instantaneous values, the SSCs oscillated between 1 and 2138 mg L −1 , although they were below 25 mg L −1 threshold of the EU Freshwater Fish Directive (78/659/EEC), replaced by the Water Framework Directive (2000/60/EC) [35] and Directive 75/440/EEC [36], most of the study period (Table 1 and Figure 5).…”
Section: Dynamics In Suspended Sediment Concentrationssupporting
confidence: 67%
See 3 more Smart Citations